2020
DOI: 10.1016/j.engstruct.2020.110189
|View full text |Cite
|
Sign up to set email alerts
|

CFDST sections with square stainless steel outer tubes under axial compression: Experimental investigation, numerical modelling and design

Abstract: The use of concrete-filled double skin tubular (CFDST) cross-sections for compression members has become increasingly popular in construction. A recently proposed innovative form of CFDST cross-section, ultilising stainless steel for the outer tube, offers the combined advantages of the composite action seen in CFDST member alongside the durability and ductility associated with stainless steel. CFDST sections with stainless steel outer tubes, for which there are currently little experimental data, are the focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 41 publications
(76 reference statements)
2
52
0
Order By: Relevance
“…A number of experimental investigation into the compressive behaviour of CFDST crosssections with stainless steel outer tubes have been carried out [9][10][11][12], but the only previous experiments on CFDST cross-sections with SHS carbon steel inner tubes and SHS/RHS lean duplex and ferritic stainless steel outer tubes (see Fig. 1), which are the focus of the present study, were reported in Wang et al [10].…”
Section: Review Of Existing Experimental Datamentioning
confidence: 99%
See 4 more Smart Citations
“…A number of experimental investigation into the compressive behaviour of CFDST crosssections with stainless steel outer tubes have been carried out [9][10][11][12], but the only previous experiments on CFDST cross-sections with SHS carbon steel inner tubes and SHS/RHS lean duplex and ferritic stainless steel outer tubes (see Fig. 1), which are the focus of the present study, were reported in Wang et al [10].…”
Section: Review Of Existing Experimental Datamentioning
confidence: 99%
“…FE models of all test specimens presented in Section 2 were established employing C3D8R [25] solid elements for the concrete and S4R [25] shell elements for the metal tubes, in line with previous numerical modelling of concrete-filled tubular members [11,12,[26][27][28][29]. A systematic mesh sensitivity study was undertaken to decide upon suitable mesh settings for the FE models, in order to produce accurate yet computationally efficient results.…”
Section: Element Types and Discretisationmentioning
confidence: 99%
See 3 more Smart Citations